2023
DOI: 10.1101/2023.02.24.529873
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multimodal decoding of human liver regeneration

Abstract: The liver has a unique ability to regenerate however in the setting of acute liver failure (ALF) this regenerative capacity is often overwhelmed and emergency liver transplantation is the only curative option. To advance our understanding of human liver regeneration and to inform design of pro-regenerative therapies, we use paired single-nuclei RNA sequencing (snRNAseq)combined with spatial profiling of healthy and ALF explant human livers to generate the first single-cell, pan-lineage atlas of human liver reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
2
3
0
Order By: Relevance
“…Our findings, together with others’ findings and despite preliminary, suggest that hepatocytes might sacrifice metabolic activity for safeguarding regenerative expansion, and that hepatocytes are equipped with flexible metabolic machinery able to adapt dynamically to tissue regeneration [31]. It is also noteworthy that our data revealed involvements of the immune, endothelial and stromal cell components in liver regeneration, which are in accordance with the current understanding [3, 10, 32], and that communication between hepatocytes and various cell populations through EVs potentially contributed to liver regeneration. Future research is needed to examine in-depth the multimodal paracrine regulation mechanisms via Hep-EVs that safeguard liver regeneration.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings, together with others’ findings and despite preliminary, suggest that hepatocytes might sacrifice metabolic activity for safeguarding regenerative expansion, and that hepatocytes are equipped with flexible metabolic machinery able to adapt dynamically to tissue regeneration [31]. It is also noteworthy that our data revealed involvements of the immune, endothelial and stromal cell components in liver regeneration, which are in accordance with the current understanding [3, 10, 32], and that communication between hepatocytes and various cell populations through EVs potentially contributed to liver regeneration. Future research is needed to examine in-depth the multimodal paracrine regulation mechanisms via Hep-EVs that safeguard liver regeneration.…”
Section: Discussionsupporting
confidence: 91%
“…Of note, we observed that QC6352 treatment increased the expression of several cytochrome transcripts that are considered markers of hepatocyte function in drug detoxification ( 88 ). We found that CYP3A4 was KDM4 regulated, and has been shown to be enriched in the pericentral region of the human liver, consistent with oxygen-driven liver zonation ( 89 ). Interestingly, in vitro assays have manipulated cytochrome expression to regulate the differentiation of hepatocyte-like cells from induced pluripotent stem cells ( 44 , 46 , 58 ).…”
Section: Discussionsupporting
confidence: 58%
“…50 ANXA2 þ hepatocytes increased following APAP injection, peaking at 42 hours in the peri-necrotic region. 50 Surviving hepatocytes adjacent to the necrotic lesions increasingly express CXCR2, which is required for hepatocyte recovery and regeneration after APAP administration. 51 HSCs are activated and proliferate earlier after APAP injection.…”
Section: Other Types Of Cellsmentioning
confidence: 99%